2019
DOI: 10.1007/jhep02(2019)178
|View full text |Cite
|
Sign up to set email alerts
|

Shift symmetries in (anti) de Sitter space

Abstract: We construct a class of extended shift symmetries for fields of all integer spins in de Sitter (dS) and anti-de Sitter (AdS) space. These generalize the shift symmetry, galileon symmetry, and special galileon symmetry of massless scalars in flat space to all symmetric tensor fields in (A)dS space. These symmetries are parametrized by generalized Killing tensors and exist for fields with particular discrete masses corresponding to the longitudinal modes of massive fields in partially massless limits. We constru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 152 publications
(330 reference statements)
3
91
0
Order By: Relevance
“…11 The two exceptional EFTs are the scalar DBI and special galileon [28] (the more general galileon EFT [27] is the σ = 2 extended shift symmetry). See [50] for a classification in dS/AdS space.…”
Section: Soft Degree σmentioning
confidence: 99%
“…11 The two exceptional EFTs are the scalar DBI and special galileon [28] (the more general galileon EFT [27] is the σ = 2 extended shift symmetry). See [50] for a classification in dS/AdS space.…”
Section: Soft Degree σmentioning
confidence: 99%
“…Interacting theories of scalars in (A)dS space with k ≤ 2 shift symmetries were studied in Ref. [21], which are generalizations of the galileon and special galileon to (A)dS space. Here we have shown that there also exist interacting vector theories with a non-abelian k = 0 shift symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Consider a free massive spin-1 field, A µ , on (A)dS 4 with mass m, as described by the Proca Lagrangian It was shown in Ref. [21] that for particular values of the mass the free theory (2.1) acquires various shift symmetries. In particular, at the mass value…”
Section: Symmetries Of the Free (A)ds Spin-1 Theorymentioning
confidence: 99%
“…For classifications of non-linearly realized symmetries in the cosmological background, using Lagrangian and algebraic methods, see [82,83]. A similar classification to the one presented in this thesis for AdS backgrounds appears in [81].…”
Section: Possibilities For Future Researchmentioning
confidence: 67%
“…While this theory propagates a ghost (and does not allow for gauge symmetry or a central extension), it might be related to a sensible EFT by including a cosmological constant: in AdS space-time there is a theory of a massive vector with a double copy of the AdS isometries as non-linear symmetries, which arises in a specific decoupling limit of massive gravity. [81,172] It would be very interesting to investigate the relations of this theory to its flat space-time counterpart discussed here. Exceptional EFTs with N = 1 supersymmetry…”
Section: Vector Goldstone Modesmentioning
confidence: 99%